Since the opposite operation of addition is subtraction you subtract. So you add 14 both sides and now z is by itself. finally just add 2 and 14 which is 16
Answer:
<h2>f(x - k) = (x - k)²⇒ k = 5</h2>
Step-by-step explanation:
f(x) + n - shift the graph n units up
f(x) - n - shift the graph n units down
f(x - n) - shift the graph n units to the right
f(x + n) - shift the graph n units to the left
==============================================
Look at the picture.
The graph has been shifted 5 units to the right.
Therefore we have f(x - 5).
Step-by-step explanation:
Some expressions that are equivalent to this is: 1 - 1/5; 2 - 1 1/5; 3 - 2 1/5; etc.